India’s Strategy to Procure Lithium to be a Leading Lithium-Ion Battery Manufacturer - Shubham Gandhi; Drumil Newaskar; Rohan Apte; Preet Aligave (International Journal of Engineering and Management Research, 2021)
Lithium is one of the foremost valuable metal which is widely used for manufacturing batteries and also has other uses in solar panels, ceramics, glasses and pharmaceuticals. Lithium is third most abundant element after hydrogen and helium but the most lithium deposits are only in Bolivia (21 million tons), Argentina (17 million tons), Chile (9 million tons), Australia (6.8 million tons), China (4.5 million tons). Bolivia, Argentina, Chile forms so called lithium triangle. Due to depleting reserves of fossil fuels and its harmful impact on the environment has forced the globe to shift to Lithium-ion batteries which is much eco-friendlier alternative. India’s push for electric vehicles (EV) may cause a considerable change in its energy security priorities, with securing lithium supplies, a key material for creating batteries, becoming as important as buying oil and gas fields overseas. India doesn't have enough lithium reserves for manufacturing lithium-ion batteries. The majority electric vehicles within the country run on imported batteries, mostly from China. At present a lithium-ion battery accounts for 40% of the overall cost of an electrical vehicle. Khanij Bidesh Pvt Ltd is a venture firm of three central public sector enterprises namely National Aluminum Company (Nalco), Hindustan Copper Ltd (HCL), Mineral Exploration Company Ltd (MECL). The KABIL would do identification, acquisition, exploration, development, mining and processing of strategic minerals overseas for commercial use and meeting country’s requirement of those minerals. The mission is to not allow India to fall in a very vulnerable position with a probable threat of supply squeeze as went on within the case of petroleum, with India being the world’s third largest oil importer and to amass cobalt and lithium mines in addition on get into purchase agreements of those minerals. This may help in achieving resource security with regard to strategic minerals.